Clinical outcomes of self-expandable vs. balloon-expandable TAVI for severe aortic stenosis. Issue 3 (3rd May 2020) - Tham, Jodie Li Mei; Adams, Heath; Paleri, Sarang; Wright, Christine; Dimitriou, Jim; Newcomb, Andrew; MacIsaac, Andrew I.; Whitbourn, Robert J.; Palmer, Sonny C.
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is an established therapy for patients with severe aortic stenosis (AS). There is limited data exploring differences in outcomes post-TAVI SEV vs. BEV. This study compared procedural success and 30-d clinical outcomes self-expandable valves (SEV), vs. balloon-expandable valves (BEV) for patients with severe AS. Methods: Retrospective analysis was undertaken of patients receiving TAVI at St Vincent's Hospital, Melbourne between August 2009 and May 2018. The primary endpoints included procedural success, clinical outcomes and complication rates at 30-d. Results: Out of 151 patients undergoing TAVI, 70 received (46.3%) SEV (Medtronic CoreValve & Evolut-R) and 81 (53.6%) BEV (Edwards SAPIEN-XT & S3). The mean Society of Thoracic Surgery (STS) risk score did not differ between the groups, SEV (83.6 ± 4.9 years, STS 4.4 ± 3.8) compared to BEV (82.3 ± 5.8 years, STS 4.9 ± 4.9). Procedural success was similar SEV 67 (95.7%) vs. BEV 78 (96.3%). Rates of ≥ moderate paravalvular aortic regurgitation (PAR) at 30-d were significantly higher in SEV compared to BEV (6.7 vs. 0.0%; p = .02). SEV patients had higher rates of pacemaker insertion (36.4 vs. 9.5%; p = .001) and stroke rates (12.4 vs. 1.4%; p = .04) compared to BEV patients. The difference in 30-d mortality between the two groups was similar (SEV 4.6% vs. BEV 1.3%; p = .23). Conclusions: This real-world retrospective analysis demonstrates higher rates of ≥ moderate PAR, stroke and pacemaker insertion with SEV compared to BEV at 30 d post-TAVI for severe symptomatic AS.